Digital transformation of higher education: challenges of the time (Journal of Educational Sciences, 2024)
The presented article is the result of scientific work, which explores the key aspects and characteristics of the process of digital transformation in the modern higher education system. Since 2018, the Republic of Kazakhstan has been implementing the "Digital Kazakhstan" program, which focuses on five main areas: "Digitalization of economic sectors," "Transition to a digital state," "Implementation of the Digital Silk Road," "Development of human capital," and "Creation of an innovation ecosystem."The review of scientific and theoretical literature has helped to underscore the role of information technology in the digital transformation of higher education N.Yu. Ignatova pointed out this role, where education is one of the basic areas of human life. These include 1. Digital advantage - building intellectual capital. 2. Problems of IT education. 3. Pandemic and digital transformation in education. 4. Cluster principles of education development.The primary aim of our research is to examine the role of information technology in the digital transformation of higher education. The primary materials for the study included scientific and theoretical resources, university accounting records, and completed forms with respondents' answers gathered through socio-pedagogical diagnostics. Research methods include analyzing psychological, pedagogical, socio-economic, and technical literature related to the research problem; conducting comparative and system-structural analyses; and utilizing sociological surveys and questionnaires.The results include a description of the transformational processes occurring within the higher education system, the terminology framework of didactics in the modern educational process in light of digital transformation, and findings from a sociological survey of students and faculty at the Pedagogical Department of K. Zhubanov Aktobe Regional University.Key words: digital transformation, higher education, didactics, transformational processes, IT-education.